Distribution of 14C-Photosynthetate in the Shoot of Vitis vinifera L. cv Cabernet Sauvignon I. The Effect of Leaf Position and Developmental Stage of the Vine - HUNTER, J.J.; VISSER, J.H. (South African Journal of Enology and Viticulture, 2017)
The distribution of photosynthetates, originating in leaves of different parts of the shoot of Vi tis vinifera L. cv Cabernet Sauvignon at berry set, pea size, veraison and ripeness stages, was investigated. Specific photosynthetic activity of the "CO,-treated leaves gradually decreased during the season. Photosynthetates were hoarded in the leaves at berry set, but were increasingly diverted to the bunches after that. The apical leaves displayed the Itlghes.t.photosynthesis. The leaves opposite and below the bunches accumulated very little photosynthetafes, especially from veraison to ripeness. Redistribution of photosynthetates among the basal, middle and apical leaves was generally very restricted at all stages. Multidirectional distribution from the site of application of 14CO, occurred at berry set stage, while from pea size to ripeness photosynthetates were mainly translocated basipetally. Highest accumulation in the bunches occurred at veraison, while the basal leaves were primarily used to nourish the bunch.